Impact of soil residual herbicides on establishment of interseeded/overseeded cover crops in corn and weed control efficacy - Silva, Tatiane Severo (Brasil, 2023)
Preemergence (PRE) herbicides with soil residual activity resurge as a foundation for early-season weed control in corn; however, there is a potential injury from soil residual PRE herbicides to interseeded/overseeded cover crops, a cultural practice of interest to corn growers. Field experiments were conducted at Janesville and Lancaster, WI in 2021 and 2022 (4 site-years) to evaluate the weed control efficacy of solo (single site of action [SOA]) and premix (two or more SOAs) PRE herbicides in conventional tillage corn systems. Greenhouse bioassays were conducted in 2021 and 2022 to assess the impact of these PRE herbicides on the establishment of interseeded cover crops. Treatments consisted of 18 PRE herbicides plus a nontreated check. Annual rye (Lolium multiflorum L.), cereal rye (Secale cereale L.), radish (Raphanus sativus L.), and red clover (Trifolium pratense L.) were used as bioindicators. PRE herbicides with two (78%) and three (81%) SOAs provided higher weed control than PRE herbicides with a single SOA (68%), indicating at least two SOAs are needed in a premix to enhance weed control. Cereal rye was the least sensitive species to PRE herbicides. Annual rye, radish, and red clover were more sensitive to PRE herbicides containing two and three SOAs than herbicides with a single SOA. PRE herbicide efficacy varied according to the weed species, but the premixes appeared as a more reliable option to improve early-season weed control in conventional tillage corn systems. However, cover crop species should be carefully selected depending on the residual PRE herbicide when interseeded or overseeded into corn. Additional field studies are needed to validate these results in different environments and support recommendations to growers interested in this system
Impacto de herbicidas residuais do solo no estabelecimento de culturas de cobertura intercaladas em milho e eficácia no controle de plantas daninhas
Keywords: CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; bioassay; carryover; cover crop interseeding; preemergence herbicides; Zea mays L.; bioensaio; carryover; cultura de cobertura intercalada; herbicidas pré-emergentes; Zea mays L.